PERKEMBANGAN PENDIDIKAN ISLAM (Perspektif Pendidikan Transformatif antara Kenyataan dan Harapan) - Toriqularif, Muhammad (STAI AL FALAH Banjarbaru, 2017)
In Indonesia, education should be developed as objective, visionary and based on the philosophy of state objectives. Education should be mainstreamed by the unification of education with the social issues that society is struggling to create and to provide perspective for the future. Such education is read as a social entity laid out within the framework of the transformation of Indonesian society. In the current atmosphere of the education system, it seems that Indonesia is still at a crossroads. On the one hand there is a direction for building community-based, process-oriented education and enabling development towards transformative education (with very hard work?), But on the other hand, there are still elements of results-oriented and centralistic rules such as the National Exam with all the impact of its implementation. Keywords: Islamic Education, Transformative Education.